Hard-to-recycle plastics in the automotive sector: Economic, environmental and technical analyses of possible actions. (25th March 2023) - Ravina, Marco; Bianco, Isabella; Ruffino, Barbara; Minardi, Marta; Panepinto, Deborah; Zanetti, Mariachiara
Abstract: The use of plastics in the automotive industry is favoured by their relatively low cost, but a sustainable treatment at their end of life is still challenging. The objective of this study is to contribute to the identification of best practices to increase the recovery rate of plastic materials from end-of-life vehicles (ELVs). European regulations for ELVs foresee that the reuse/recovery and reuse/recycling had to be increased to a minimum of 95% and 85% of the vehicle weight respectively by 2015. Three areas with room for possible improvement were identified in this study: the dismantling phase, the recycling processes, and the material recovery from automotive shredder residues (ASRs) as solid recovered fuels (SRFs). The economic feasibility of recovering specific plastic components from ELVs was assessed using a criterion based on the cost of dismantling, recycling and disposal of the components, as well as the environmental costs of the processes. Based on the results, disassembly and recycling could be cost-effective for a disassembly time below 180 s and a component mass above 600 g. For the recycling processes, the Life Cycle Assessment (LCA) methodology was applied to evaluate the environmental impacts of recycling HDPE from fuel tanks, polyamides PA6/PA66 and PET from automotive components. As the climate change indicator is concerned, Tthe LCA study showed that the impact for 1 kg of these secondary raw materials is respectively of 0.83, 0.16/0.17 and 2.17 kg CO2 eq, obtained from these fractions resulting more sustainable than the respective virgin materials. Electricity consumption was among the main contributors to the potential environmental impacts. The characterization process of ASRs was conducted to assess their compliance to certain types of SRFs. According to the results of the industrial tests, the treatment facility can recover only around 74% of an ELV. The characteristics of ASRs were compliant to be assimilated to a SRF. This study showed that the amount of plastics recoverable from ELVs has the potential to increase thus facilitating the fulfilment of EU recovery targets. Graphical abstract: Image 1 Highlights: The objective was to increase the recovery of plastics from end-of-life vehicles. Techno-economic analysis on components showed the influence of environmental costs. LCA of HDPE, PA6/PA66 and PET showed higher sustainability if plastic is recycled. Characterization showed that shredder residues can be assimilated to a recovered fuel. It was showed that plastic recovery from end-of-life vehicles can be improved.